Kualitas Semen Segar Itik Mojosari (Anas Platyrhyncos javanicus) pada Pembatasan Pemberian Pakan - Ulupi, N.; Ketaren, P. P.; Naji, O. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
The high quality of semen is important to support fertilization and semen collection for the insemination. One of the factors influencing the semen quality is feed. The feed shortages and the excess of feed, both of them affect on the semen production and its quality. So the aim of this study was to evaluate the effect of feed restriction on the semen characteristics of Mojosari duck. 60 Mojosari ducks(male) were used. They were reared from 4-39 weeks age. This experiment used complete randomize design.As treatment was the restriction on feeding, that consist of four levels : ad libitum (100%) for starter-layer period (P1), feed on starter-grower 100%, layer 85% (P2), feed on starter-grower85%, layer 100% (P3), and feed on starter-layer 85% (P4). The result of this study showed that the treatments did not significantly affect on volume semen per ejaculat, spermatozoa concentration, total spermatozoa per ejaculat, motility, viability, and percentage of spermatozoa abnormality. Spermatozoa without tail on P1 was higher significant than those on another treatments (P2, P3, and P4). This study indicated that feed restriction (85% adlibitum) from starter-layer period (P4) on the Mojosari duck was sufficient to produce semen with high quality.